Self-Efficacy of Proficient Public Secondary School Teachers in the Philippines, A Sequential Explanatory Study - Pelingon, Keith Frances R.; Contreras, Clarisse M.; Moreno, Enigo G.; Dayrit, Brian D.; Mallari, Jomarie B.; Toledano, Leo G.; Dominado, Noel L. (Future Science / FSH-PH Publications, 2024)
This study aimed to identify the areas where proficient teachers struggle the most and the areas where they feel confident regarding influence in decision-making, instructional, disciplinary, parental involvement, community involvement, and a positive school climate. A mixed-method of sequential explanatory design was utilized, involving 70 secondary high school teachers in the Cluster I Schools Division of Pampanga. The study’s findings demonstrated that teachers are more comfortable and feel more competent and confident in areas like instruction and a positive school climate, where they have more direct control over the conduct and learning of their students. On the other hand, the respondents seemed to be reasonably confident in their ability to influence decisions made within the educational institution. This could be due to several factors, including their experience, relationships with other staff members, or participation in committees that make decisions for the organization. The study highlighted the importance of maintaining collaboration and support among educators, administrators, and the entire school community to foster an environment that values ongoing learning and effective teaching strategies. Lastly, this study emphasized how important teacher self-efficacy is in determining effective teaching practices, especially for experienced teachers. It also emphasized the importance of recognizing and providing targeted support for teachers' strengths to build their confidence and ultimately improve student achievement. The research suggests that schools should give priority to programs that increase teacher self-efficacy through mentorship programs, targeted professional development, and building a supportive school culture. These efforts will ultimately increase instructional effectiveness and improve the teachers’ overall confidence in teaching.